Association of different physical activity domains on all-cause mortality in adults participating in primary care in the Brazilian National Health System: 4-Year follow-up - Turi, Bruna C. [UNESP]; Codogno, Jamile S. [UNESP]; Fernandes, Romulo A. [UNESP]; Sui, Xuemei; Lavie, Carl J.; Blair, Steven N.; Monteiro, Henrique L. [UNESP] (Human Kinetics, 2017)
Background: Evidence has shown that physical activity (PA) is associated with low mortality risk. However, data about reduced mortality due to PA are scarce in developing countries and the dose-response relationship between PA from different domains and all-cause mortality remains unclear. Thus, the aim of this study is to investigate the association of PA from different domains on all-cause mortality among Brazilian adults. Methods: 679 males and females composed the study sample. Participants were divided into quartile groups according to PA from different domains (occupational, sports, and leisure-time). Medical records were used to identify the cause of the death. Cox regression analysis was performed to determine the independent associations of PA from different domains and all-cause mortality. Results: During the follow-up period, 59 participants died. The most prevalent cause of death was circulatory system diseases (n = 20; 33.9% [21.8%-45.9%]). Higher scores of occupational (HR= 0.45 [95% CI: 0.20-0.97]), sports (HR= 0.44 [95% CI: 0.20-0.95]) and overall PA (HR= 0.40 [95% CI: 0.17-0.90]) were associated with lower mortality, even after adjustment for confounders. Conclusions: The findings in this study showed the importance of being active in different domains to reduce mortality risk.
Keywords: Epidemiology; Mortality; Physical activity; Public health